P‐125: Influence of Line Shape on the Durability of Bending Lines on Flexible OLED Panels. Issue 1 (25th September 2020) - Chen, Lin Dou; Peng, Tao; Ma, Yu Fang; Han, Qing; Peng, Guanzhen
Abstract : Experiments were conducted to test the durability of bending line with different shapes on the bending area of 5.85 inch flexible OLED panel. Results showed that Z shape lines owned the best performance. Additionally, other shapes were further discussed.